The Lorenz curve: a novel method for understanding viral load distribution at the population level. (14th January 2017) - Christopoulos, Katerina A.; Hartogensis, Wendy; Glidden, David V.; Pilcher, Christopher D.; Gandhi, Monica; Geng, Elvin H.
Abstract : Existing HIV care cascade metrics fail to capture whether viremia is equally distributed in a population or concentrated within groups. We applied the Lorenz curve, which has been used to describe disparities in the distribution of income and other resources, to the distribution of viremia in a safety-net HIV clinic in 2012. Among 1855 established clinic patients, 1% of the population held 50% of the virus and 10% of the population held 94% of virus.